Endovascular Therapy Versus Medical Therapy Alone for Basilar Artery Stroke: A Systematic Review and Meta‐Analysis Through Nested Knowledge - Gautam Adusumilli; John M. Pederson; Nicole Hardy; Kevin M. Kallmes; Kristen Hutchison; Hassan Kobeissi; Daniel M. Heiferman; David Kallmes; Waleed Brinjikji; Gregory W. Albers; Jeremy J. Heit (Stroke: Vascular and Interventional Neurology, 2022)
Background Endovascular thrombectomy (EVT) is an effective treatment for acute ischemic stroke attributable to the anterior circulation large‐vessel occlusion. Randomized trials of patients with posterior circulation large‐vessel occlusion (PC‐LVO) have failed to show a benefit of EVT over medical therapy (MEDT). We performed a systematic review and meta‐analysis to understand better whether EVT is beneficial for PC‐LVO. Methods Using the Nested Knowledge AutoLit living review platform, we identified randomized control trials and prospective studies that reported functional outcomes in patients with PC‐LVO treated with EVT versus MEDT. The primary outcome variable was 90‐day modified Rankin scale score of 0 to 3, and secondary outcome variables included 90‐day modified Rankin scale score of 0 to 2, 90‐day mortality, and rate of symptomatic intracranial hemorrhage. A separate random effects model was fit for each outcome measure to calculate pooled odds ratios. Results Three studies with 1248 patients, 860 in the EVT arm and 388 in the MEDT arm, were included in the meta‐analysis. The favorable outcome rate (modified Rankin scale score of 0–3) in patients undergoing EVT was 39.9% (95% CI, 30.6%–50.1%) versus 24.5% in patients undergoing MEDT (95% CI, 9.6%–49.8%). Patients undergoing EVT had higher modified Rankin scale score of 0 to 2 rates (31.8% [95% CI, 25.7%–38.5%] versus 19.7% [95% CI, 7.4%–42.7%]) and lower mortality (42.1% [95% CI, 35.9%–48.6%] versus 52.8% [95% CI, 33.3%–71.5%]) compared with patients undergoing MEDT, but neither result was statistically significant. Patients undergoing EVT were more likely to develop symptomatic intracranial hemorrhage (odds ratio, 10.36; 95% CI, 3.92–27.40). Conclusions EVT treatment of PC‐LVO trended toward superior functional outcomes and reduced mortality compared with MEDT despite a trend toward increased symptomatic intracranial hemorrhage in patients undergoing EVT. Existing randomized and prospective studies are insufficiently powered to demonstrate a benefit of EVT over MEDT in patients with PC‐LVO.